Studies on the interrelationship between the syntheses of noradrenaline and metaraminol - Johnson, G. E. (1970)
1. Experiments were conducted to determine the influence of the rate of noradrenaline synthesis on the conversion of alpha-methyl-m-tyrosine to metaraminol. 2. Male Wistar rats, 175-200 g, were placed into four groups and treated with (1) alpha-methyl-p-tyrosine methyl ester, 250 mg/kg; (2) DL-alpha-methyl-m-tyrosine, 400 mg/kg; (3) alpha-methyl-p-tyrosine methyl ester, 250 mg/kg plus DL-alpha-methyl-m-tyrosine, 400 mg/kg; or (4) an equivalent volume of injection vehicle. All solutions were injected intraperitoneally. 3. Immediately after treatment half of the rats were transferred to 4° C with the remaining animals being kept at 27° C. 4. The rats were killed 4, 8 and 12 h after injection, the brains, hearts, spleens and adrenals removed and analysed for adrenaline, noradrenaline, metaraminol and alpha-methyl-m-tyramine. 5. In virtually all cases, both during rest (27° C) and sympathetic stress (4° C), treatment of the rats with alpha-methyl-p-tyrosine methyl ester increased the amount of metaraminol formed from alpha-methyl-m-tyrosine. The only organ not containing increased quantities of metaraminol in the presence of alpha-methyl-p-tyrosine methyl ester was the adrenals, taken from the rats kept at 27° C. Adrenals removed from the cold-exposed rats contained more metaraminol when alpha-methyl-p-tyrosine methyl ester was combined with alpha-methyl-m-tyrosine than when alpha-methyl-m-tyrosine was used alone. 6. These results demonstrate that the inhibition of noradrenaline synthesis, by treatment with the tyrosine hydroxylase inhibitor alpha-methyl-p-tyrosine methyl ester, increased the conversion of alpha-methyl-m-tyrosine to metaraminol. It is concluded that inhibiting the formation of dopa allowed increased amounts of alpha-methyl-m-tyrosine to enter the biosynthetic pathway. These results support the false sympathetic transmitter concept advanced for metaraminol.